2016
DOI: 10.1590/0103-8478cr20160022
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle frozen autograft for limb sparing surgery in a dog with femoral osteosarcoma

Abstract: Osteosarcoma (OSA) is the most common bone tumor diagnosed in dogs and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The long-term prognosis is also good, with reported postoperative complications such as fractures (19.4%), deep infection (11.1%), and local soft tissue recurrence (11.1%), with no recurrence detected within the liquid nitrogen-treated autogenous bone [ 4 ]. Limited reports in the veterinary field also indicated good postoperative mandibular and gait function improvements in cases where reconstruction methods utilizing liquid nitrogen-treated autologous bone were applied [ 1 , 3 , 12 , 16 ]. Although none of the aforementioned complications were observed, exudate was observed postoperatively in Case 1 and screw breakage in Case 2.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…The long-term prognosis is also good, with reported postoperative complications such as fractures (19.4%), deep infection (11.1%), and local soft tissue recurrence (11.1%), with no recurrence detected within the liquid nitrogen-treated autogenous bone [ 4 ]. Limited reports in the veterinary field also indicated good postoperative mandibular and gait function improvements in cases where reconstruction methods utilizing liquid nitrogen-treated autologous bone were applied [ 1 , 3 , 12 , 16 ]. Although none of the aforementioned complications were observed, exudate was observed postoperatively in Case 1 and screw breakage in Case 2.…”
Section: Casementioning
confidence: 99%
“…In Tsuchiya et al .’s protocol, the extracted affected bone is treated with liquid nitrogen at −196°C for 20 min, left at a room temperature of 20°C for 15 min, and incubated in a saline solution at 30°C for 10 min, for a total duration of 45 min [ 21 ]. In veterinary medicine, tumor bone has been reconstructed using liquid nitrogen cryoprocessed bone tissue in the scapula in cats [ 1 ] and the mandible [ 12 ], femur [ 3 ], and tibia [ 16 ] in dogs. However, there are few reports of reconstructive surgery using liquid nitrogen-treated autologous bone in the veterinary field.…”
mentioning
confidence: 99%
“…These are: Chen at. Al [2][3][4][5][7][8][9][10][11][12][13][14]. The animals described in this review, the animals were middle aged to elderly and medium to large size, except for one case of a Maltese dog reported by Teixeira et al [18].…”
Section: Incidence Of Osteosarcoma In Dogsmentioning
confidence: 99%
“…The study by Ferrigno et al [8] still includes abdominal ultrasound. The dentification of metastases and other diseases is fundamental to planning the treatment and, consequently, obtaining better prognosis [13,14,21,23] Regarding the treatment, Ferrigno et al [8] and Gôuvea et al [2], reported that limb preservation surgery, considered to be the best choice of treatment, as well as emphasized by Ziliotto et al [7], when combined with adjuvant chemotherapy provided a longer survival. In addition, the study by Ziliotto et al [7] has improved the surgical technique focused on the preservation of the bone implant in glycerin, which proved to be efficient for this purpose.…”
Section: Surgical Approach and Diagnosis Through Imaging Testsmentioning
confidence: 99%
“…Additionally, the incidence of complications, such as postoperative infection and construct failure, is high [5, 7]. To the best of our knowledge, there have been only two reports of frozen autograft reconstruction in dogs [2, 8], but none in cats.…”
mentioning
confidence: 99%